Usulan Peningkatan Produktivitas Pada Proses Pencucian Produk HDD Dengan Mesin Otomatis - Qomarotun Nurlaila (PROFISIENSI : Jurnal Program Studi Teknik Industri, 2020)
PT. ABC is manufacture company that produce HDD (Hard Disk Drive) product with rubber as raw material. One of production process is process to washing product. Current practice, washing process use manual machine which process depend on worker’s performance. Productivity of washing process need to improved. Engineering propose automation washing machine to improve it. Effect after change washing machine from manual to automation such as productivity increase 33.6 times (from 2,199  to 38,000 pc/man/hour), daily output increase  3.3 times (from 92,337  to 399,000 pcs / hour), man power reduce 3.5 Person (from 4 to 0.5 person) and man power cost reduce Rp. 28,700,000.- / month (from Rp. 32,800,000.- to Rp 4,100,000.- /month).